Teaching/learning in a new technological context: a study in higher education - Costa, Carolina Simões da (2020)
Today’s students of higher education are considered digital natives. They have a wide array of technologies at their disposal that are used in their day-to-day lives in very different contexts; including recreation, work and academic. This scenario promotes a change of culture by the main actors associated with the Teaching/Learning process. This prompted the development of the present thesis which aims to evaluate the degree of use and acceptance of technologies supporting the Teaching/Learning process in Higher Education Institutions (HEI). The methodology used when conducting this study was based initially on a review of the specialized literature, identifying the three main technological generations supporting the Teaching/Learning process: Learning Management Systems (LMS), Web 2.0 technologies and Massive Open Online Courses (MOOCs). Subsequently, the technologies recognized as the most relevant within each of these generations have been the subject of (i) a systematic literature review, (ii) a content analysis elaborated on the platforms/technologies used in international Higher Education Institutions, and (iii) an empirical work conducted at a Portuguese Higher Education Institution. Concerning the latter, an understanding of the behavior of the two main players involved in the Teaching/Learning process (students and teachers) was particularly sought after. Therefore, studies were conducted on (i) the students’ use of the main technologies, (ii) the students’ acceptance of some of these technologies in the context of Teaching/Learning and (iii) the use and acceptance of the technologies by teachers. The results indicated that the Moodle platform is the LMS most used in Higher Education Institutions. In this context, the platform is mostly used as a content repository and a communication channel. As for Web 2.0, Video Sharing, Social Networks and Wikis were proven to be the technologies most used by students and teachers. The results also revealed that the technologies in question are well accepted by both parties, thus showing that their adoption could benefit the Teaching/Learning process in the new technological paradigm. Regarding the MOOCs, few teachers showed knowledge of the concept and no teachers who had created these type of courses were identified. This study resulted in the development of seven scientific works with peer review, being five scientific papers published or submitted to international scientific journals and two chapters published in international books. These scientific works constitute an integral part of this doctoral thesis.